Hamartomas and midline anomalies in association with infantile hemangiomas, PHACE, and LUMBAR syndromes. Issue 1 (20th October 2019) - Stefanko, Nicole S.; Davies, Olivia M.T.; Beato, Maria Jose; Blei, Francine; Drolet, Beth A.; Fairley, Janet; Frieden, Ilona J.; Galligan, Eloise R.; Goddard, Deborah; Howard, Renee; Husain, Sameera; Lauren, Christine T.; et al.
Abstract: Background/Objective: The pathogenesis of infantile hemangiomas (IH), PHACE, and LUMBAR syndromes remains unknown. We aim to describe histopathologic features of midline anomalies associated with IH, including patients with PHACE and LUMBAR syndromes. Methods: A multicenter retrospective chart review was performed to identify patients with IH, PHACE, and LUMBAR syndrome with histopathologic specimens from sternal or midline anomalies. A total of 18 midline lesions from 13 patients were included. Out of 18, 14 midline lesions underwent both histopathologic and clinical review. Three hamartoma‐like chin plaques and one supraumbilical raphe underwent only clinical review. Results: All 13 patients had midline lesions and IH. Histopathologic diagnoses were as follows: rhabdomyomatous mesenchymal hamartoma (3), folliculosebaceous cystic hamartoma (1), fibroepithelial polyp (1), verrucous epidermal hyperplasia with vascular proliferation and fibroplasia (1), congenital midline cervical cleft (1), pericardium with fibrosis (1), fibrous components with increased collagen (1), atrophic skin/membrane (3), angiolipomatous mass with neural components (1), and lipomatous mass (1). Due to the retrospective nature of this study, it was not possible to obtain pathology slides for all midline lesions that had previously been biopsied or resected. We show clinically and histopathologically a new association between PHACE syndrome and rhabdomyomatous mesenchymal hamartoma (RMH), in addition to demonstrating the association between PHACE syndrome and chin hamartomas. We also display histopathologic findings seen in midline lesions resected from LUMBAR patients. Conclusion: Rhabdomyomatous mesenchymal hamartoma is thought to be related to aberrations of mesenchymal cells during development; therefore, this may provide clues to the pathogenesis of IH and related syndromes.